Marketing Sustainability to the Base: Exploring Drivers of Green Behavior Among Indonesia’s Low Socioeconomic Populations - Zefanya, Abraham; Adiwijaya, Karto (Politeknik Negeri Bandung, 2025)
This study investigates the factors influencing the adoption of green behavior among low-income populations in Indonesia, aiming to inform more inclusive sustainability strategies. Employing a qualitative phenomenological methodology, in-depth interviews were conducted with 10 participants in Jakarta, focusing on efforts to reduce single-use plastic consumption. The results reveal that while environmental education enhances green behavioral intentions, its influence on actual behavior change is constrained by financial limitations and a reluctance to incur higher costs unless alternatives are unavailable or personal expectations are fulfilled. Additionally, messages emphasizing personal benefits resonate more than environmental appeals, and local community-driven social norms are more effective in promoting green behavior than external influencers. Policies and regulations were found to moderate the conversion of intention into behavior, while perceived needs and ease of use of conventional items, coupled with financial constraints, form behavioral control factors that can directly affect green behavior adoption. This research extends the Theory of Planned Behavior by providing nuanced insights into green behavior adoption in low-income contexts, offering practical implications for policymakers and stakeholders to design inclusive and effective sustainability initiatives.